Kuchiguse in the Nintendo Switch Console Game - Study of Onomatopoeic in â€œAtsumare: Doubutsu no Moriâ€ - Resha, Firdhani; Firmansyah, Dian Bayu; Kurniawan, Eko (Universitas Pendidikan Indonesia (Indonesia University of Education), 2021)
This research aims to describe and classify Japanese onomatopoeia, which appear in the form ofÂ kuchiguseÂ from animal characters in theÂ Atsumare: Doubutsu no MoriÂ console game. The method used is a qualitative descriptive research method with data collection techniques is the observation note technique. Based on the results of this research, it can be concluded that the onomatopoeicÂ kuchiguseÂ that appears the most is based on characters onomatopoeic found 62Â kuchiguseÂ originating from onomatopoeia followed byÂ giyougo, gijougo, giseigo, giongo,Â andÂ gitaigo. Each animal pronounces onomatopoeia likeÂ SacchiÂ pronouncingÂ giseigoÂ onomatopoeia,Â MeruborunÂ pronouncingÂ giongoÂ onomatopoeia, andÂ AndesuÂ pronouncingÂ gitaigoÂ onomatopoeia. The spokenÂ kuchiguseÂ can be derived from onomatopoeia and the spoken onomatopoeia by the animal characters has no meaning to the sentence previously spoken. The use of onomatopoeia ofÂ kuchiguseÂ as vocabulary inÂ Atsumare: Doubutsu no MoriÂ is another variation of idiolect.